2017
DOI: 10.21315/mjms2017.24.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Guided versus Conventional Surgical Resection of High Grade Glioma: A Single-Centre, 7-Year, Comparative Effectiveness Study

Abstract: To cite this article: Ng WP, Liew BS, Idris Z, Rosman AK. Fluorescence-guided versus conventional surgical resection of high grade glioma: a single-centre, 7-Year, comparative effectiveness study. Results: Significant longer survival time (months) was observed in the FG group compared with the conventional group (12 months versus 8 months, P < 0.020). Even without adjuvant therapy, HGG patients from FG group survived longer than those from the conventional group (8 months versus 3 months, P = 0.006). No signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Of the 23 studies, 9 reported a mean OS period in months ranging from 10 to 22 months (5, 25, 26, 31, 34, 4447). One of the studies, by Stummer et al (31), stratified the survival analysis by age (55 years of age and younger vs. older than 55 years).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 23 studies, 9 reported a mean OS period in months ranging from 10 to 22 months (5, 25, 26, 31, 34, 4447). One of the studies, by Stummer et al (31), stratified the survival analysis by age (55 years of age and younger vs. older than 55 years).…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis in the group of patients with primary HGG who underwent 5-ALA–guided resection showed a mean OS of 16.3 months (95% CI, 14.1–18.5 months; P < 0.001) (Figure 5). Five studies (seven distinct 5-ALA groups) were available for comparison of OS (measured as a mean survival difference) between 5-ALA vs. control groups (25, 31, 34, 46, 47). No significant heterogeneity was noted across these groups ( I 2 = 0%; P = 0.47); hence, we used a fixed-effects model.…”
Section: Resultsmentioning
confidence: 99%
“…Intraoperative PpIX fluorescence-guided resection gives longer progression-free survival. Two studies from 2017 showed preferential overall survival with 5-ALA guided resection [14,15].…”
Section: Intraoperative Fluorescence Tumor Demarcationmentioning
confidence: 99%
“…5-ALA use in glioma surgery was reviewed twice in 2017 [15,29]. Four papers published in 2018 recounted the various factors active in determining the degree of GB cells’ PpIX content [2,3,4,5].…”
Section: Intraoperative Fluorescence Tumor Demarcationmentioning
confidence: 99%
“…5-ALA use in glioma surgery was reviewed twice in 2017 [15,29]. Four papers published in 2018 recounted the various factors active in determining degree of GB cells' PpIX content [2][3][4][5].…”
Section: Intraoperative Fluorescence Tumor Demarcationmentioning
confidence: 99%